Pengaruh Ukuran Perusahaan, Likuiditas, Profitabilitas dan Leverage Terhadap Struktur Modal pada Perusahaan Basic Industry and Chemicals - Arius Zai; Jessica Vanesia Sinulingga; Lucy Mulyati Lumban Gaol; Ike Rukmana Sari; Wenny Anggeresia Ginting (IPM2KPE, 2023)
The aim of this research is to examine the influence of company size, liquidity, profitability and leverage on the capital structure of basic industry and chemicals companies on the Indonesian stock exchange for the period 2019-2021. The data processing method used in this research is Multiple Linear Regression. The results of this study found that liquidity has an influence on capital structure. Company Size, Profitability, Leverage do not have a significant influence on Capital Structure. The conclusion is that the R-Square coefficient of determination (R2) is 0.280 or 28% and the remaining 72% is explained by other variables or factors. Keywords: Leverage, Liquidity, Profitability, Capital Structure Company Size